An exploratory study into the role of leadership, organisation and technology as knowledge management enablers: implications for local criminal justice boards. - Fanthorpe, Rachel (2008)
Political pressure, enforced financial constraints, challenging performance targets; changes in the expected modes of delivery and increased ÃÂÃÂ¢ÃÂÃÂÃÂÃÂcustomerÃÂÃÂ¢ÃÂÃÂÃÂÃÂ expectations are forcing Criminal Justice agencies towards new ways of thinking about the way they are managed; hence the joining up of agencies into Local Criminal Justice Boards to deliver better performance and a customer focussed approach. Fundamental to the success of LCJBs is the creation and sharing of knowledge across organisational boundaries as no agency operates in isolation. The objective of the study was to identify and explore the main barriers and enablers to effective knowledge management within and across local criminal justice boards (LCJBs) and to identify current practice for future learning. Using a mixed methods approach combining interviews, secondary research and a quantitative survey a research model was developed that identified leadership, organisation and technology as key enablers to effective knowledge management. Within these key enablers a number of critical success factors were identified. From the findings it is evident that many of the critical success factors identified are in place or are developing concepts within the LCJBs studied. A number of barriers were also identified, such as little evidence of explicit commitment or resource in place to support knowledge management activities. This study also suggests that LCJBs are on the right path to developing a knowledge ecology from which more focussed knowledge management activity can evolve. LCJBs are well positioned within the criminal justice system to take forward and support agencies in developing and using knowledge management approaches to help support service delivery improvements and deliver systemic change. A number of recommendations are provided to enable practitioners to further develop a more cohesive and sustainable approach to knowledge creation and sharing.